Analisis heteroplasmy DNA mitokondria pulpa gigi pada identifikasi personal forensik (Heteroplasmy analysis of dental pulp mitochondrial DNA in forensic personal identification) - Ardyni Febri K; Retno Pudji Rahayu; Agung Sosiawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Mitochondrial DNA (mtDNA) sequence analysis of the hypervariable control region has been shown to be an effective tool for personal identification. The high copy and maternal mode of inheritance make mtDNA analysis particularly useful when old samples or degradation of biological samples prohibits the detection of nuclear DNA analysis. Dental pulp is covered with hard tissue such as dentin and enamel. It is highly capable of protecting the DNA and thus is extremely useful. One of the diasadvantages of mitochondrial DNA is heteroplasmy. Heteroplasmy is the presence of a mixture of more than one type of an organellar genome within a cell or individual. It can lead to ambiguity in forensic personal identification. Due to that, the evidence of heteroplasmy in dental pulp is needed. Purpose: The study was aimed to determine the heteroplasmy occurance of mitocondrial DNA in dental pulp. Methods: Blood and teeth samples were taken from 6 persons, each samples was extracted with DNAzol. DNA samples were amplified with PCR and sequencing to analyze the nucleotide sequences polymorphism of the hypervariable region 1 in mtDNA and compared with revised Cambridge Reference Sequence (rCRS). results: The dental pulp and blood nucleotide sequence of hypervariable region 1 mitochondrial DNA showed polymorphism when compared with rCRS and heteroplasmy when compared between dental pulp with blood. Conclusion: The study showed that heteroplasmy was found in mithocondrial DNA from dental pulp.latar belakang: Analisis sekuens DNA mitokondria (mtDNA) regio kontrol hypervariable telah terbukti menjadi alat efektif untuk identifikasi personal. Kopi DNA yang banyak dan pewarisan maternal membuat analisis mtDNA sangat berguna ketika sampel lama atau sampel biologis yang terdegradasi menghambat deteksi analisis DNA inti. Pulpa gigi terlindung jaringan keras seperti dentin dan enamel. Hal ini membuat pulpa mampu melindungi DNA dan dengan demikian sangat berguna untuk identifikasi. Salah satu kekurangan DNA mitokondria adalah heteroplasmy. Heteroplasmy adalah adanya campuran lebih dari satu jenis genom dalam sel atau individua. Hal ini dapat menyebabkan ambiguitas pada identifikasi pribadi forensik. Oleh sebab itu, identifikasi personal menggunakan pulpa gigi harus memperhatikan kejadian heteroplasmy. tujuan: Penelitian ini bertujuan untuk meneliti kejadian heteroplamy DNA mitokondria pada pulpa gigi. Metode: Sampel darah dan gigi diambil dari 6 orang, masing-masing sampel diekstraksi dengan metode DNAzol. Sampel DNA diamplifikasi dengan PCR dan sequencing untuk menganalisis polimorfisme urutan nukleotida di hypervariable region 1 mtDNA dan dibandingkan dengan revised Cambridge Reference Sequence (rCRS). hasil: Sekuens nukleotida pulpa gigi dan darah daerah pada hypervariable region 1 DNA mitokondria menunjukkan polimorfisme bila dibandingkan dengan rCRS dan heteroplasmy bila dibandingkan antara pulpa gigi dengan darah. Simpulan: Penelitian ini menunjukkan bahwa heteroplasmy dapat ditemukan pada DNA mitokrondia pulpa gigi.